Push-Out Bond Strength of Fiber Posts to Overflared Root Canals in Different Root Regions: Effect of Reinforcement Techniques - Mina Kahyaie Aghdam; Mahmoud Bahari; Narmin Mohammadi; Siavash Savadi Oskoee; Mohammad Esmaeel Ebrahimi chaharom (Tehran University of Medical Sciences, 2024)
Objectives: This study aimed to investigate the effect of different reinforcement techniques on the push-out bond strength of fiber posts to over-flared root canals. Materials and Methods: Forty-eight extracted human single-canal premolars were endodontically treated, over-flared, and randomly divided into four groups (N=12) including SARC: luting with self-adhesive resin cement, DCC: luting with dual-cure core build-up resin composite, CRR: relining root canal walls with bulk-fill resin composite, and DAP: relining fiber post with bulk-fill resin composite. After 24 hours, the roots were sectioned to obtain three cervical, middle, and apical 3mm slices. The push-out test was performed and failure pattern was examined. Kruskal-Wallis and post-hoc Dunn-Bonferroni tests were used for statistical analysis (P<0.05). Results: In all three regions, the lowest and highest bond strength was found in the SARC and DAP groups, respectively. In the middle region, there was a statistically significant difference between the bond strength of the SARC group and that of the DCC (P=0.044), CRR (P=0.021), and DAP (P<0.001) groups. There was no significant difference in the apical region. The lowest bond strength was observed in the apical region, and the highest was related to the cervical region. Adhesive failure was the most common failure pattern in all groups. Conclusion: Based on our results DCC, CRR and DAP methods increased bond strength in the middle and cervical sections of over-flared root regions. Considering that DCC is the easiest and most practical method, we propose that CRR and DAP can be replaced with this method in clinical procedures.